2014
DOI: 10.1111/cdep.12066
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Prosocial Behavior: Why Do Infants and Toddlers Help, Comfort, and Share?

Abstract: The early development of prosocial behavior has become a major topic in developmental psychology. Although findings on the early presence of prosocial tendencies in infants and toddlers have received much attention and the examination of their subsequent developmental pathways has fostered ample research, little is known about the mechanisms and motives that bring about the first emergence of these prosocial actions. In this article, I introduce and review theoretical approaches, then evaluate them in light of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
191
3
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(219 citation statements)
references
References 48 publications
17
191
3
8
Order By: Relevance
“…Additionally, infants' and toddlers' individual differences in Nc (300-500 ms) for viewing positive versus bad actions or in LPP/PSW (600-1,000 ms) were not related to the expression of sharing behaviors. Although sharing behaviors in infancy and toddlerhood appear to be common (47), many have questioned whether such early expressions are actually representative of morality or rather early self-regulation, compliance, and effortful control (48,49). Consistent with the latter argument, our results suggest that sharing propensity is directly related to children's temperamental effortful control.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, infants' and toddlers' individual differences in Nc (300-500 ms) for viewing positive versus bad actions or in LPP/PSW (600-1,000 ms) were not related to the expression of sharing behaviors. Although sharing behaviors in infancy and toddlerhood appear to be common (47), many have questioned whether such early expressions are actually representative of morality or rather early self-regulation, compliance, and effortful control (48,49). Consistent with the latter argument, our results suggest that sharing propensity is directly related to children's temperamental effortful control.…”
Section: Discussionsupporting
confidence: 74%
“…In attempting to account for this hallmark of human sociality, comparative and developmental psychologists have increasingly become interested in the emergence in infancy and early childhood of prosocial behavior, i.e. of 'behaviors benefiting another person without providing the helper an immediate payoff' (Paulus 2014). In particular, it has been observed that infants as early as the second year of life comfort others who are in distress (Bischof-Köhler 1988, 1991Zahn-Waxler et al 1992;Dunfield et al 2011;Dunfield and Kuhlmeier 2013;Vaish et al 2009), share food and other resources (Hay et al 1991;Levitt et al 1985), point to provide others with information (Liszkowski et al 2007), and spontaneously help others to achieve their goals (Warneken and Tomasello 2006;Svetlova et al 2010;Hepach et al 2012Hepach et al , 2016Hepach et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…3), we turn to our primary project, which is to illuminate a specific subset of models that have been proposed to account for spontaneous instrumental helping-namely models based upon 'goal alignment' (Paulus 2014). The core idea behind goal alignment models that the identification of an agent's goal leads infants to take up that goal as their own (Barresi and Moore 1996;Kenward and Gredebäck 2013;Paulus 2014;Köster et al 2015;). Our main aim will be to distinguish between two separate goal-alignment models: 'goal contagion' and 'goal slippage'.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs even when the person in need shows no distress. The idea that natural representation of other's goals or feelings provides the motivation for human prosociality is at the centre of most modern accounts of moral development (see Paulus, 2014 for review).…”
mentioning
confidence: 99%